The complete chloroplast genome of Utricularia tenuicaulis Miki (Lentibulariaceae) isolated in Korea - Jongsun Park; Hong Xi; Yongsung Kim; Sang-Tae Kim (Mitochondrial DNA. Part B. Resources, 2022)
Utricularia tenuicaulis Miki 1935 is an aquatic carnivorous plant species found in East Asia including Korea and Japan. In this study, the chloroplast genome of U. tenuicaulis was successfully sequenced. The assembled genome (153,976 bp; GC ratio, 37.0%) contains four subregions, with the large single copy (LSC; 84,596 bp; 34.9%) and small single copy (SSC; 17,946 bp; 30.5%) regions separated by 25,718 bp of inverted repeat regions (42.7%), and includes 126 genes (81 protein-coding genes, 8 rRNAs, and 37 tRNAs). Phylogenetic analyses based on the whole-chloroplast genomes of 18 species, including 17 Lentibulariaceae species and one outgroup species, suggest a close relationship between U. tenuicaulis and Utricularia macrorhiza Leconte 1824. A comparison of genomic variation between U. tenuicaulis and U. macrorhiza confirmed the validity of the specific discrimination of U. tenuicaulis.